Translation into Brazilian portuguese, cultural adaptation and validation of the oral health impact profile (OHIP-49) Tradução para a língua portuguesa, adaptação cultural e validação do "oral health impact profile" (OHIP-49) - Cássia Pérola dos Anjos Braga Pires; Marcos Bosi Ferraz; Mauro Henrique Nogueira Guimarães de Abreu (Sociedade Brasileira de Pesquisa Odontológica, 2006)
The aim of this study is to develop a Portuguese version of the OHIP-49 to be used in Brazil. The adopted methodology involves translation, back-translation, revision of the first version, cultural adaptation and evaluation of its measurement properties. The questionnaire was administered in interviews with 60 year-old and older Brazilian people. The Kendall-tau correlation coefficient was used to assess reproducibility; the Cronbach alpha coefficient was used to verify internal consistency and the Kruskal-Wallis and Mann-Whitney U tests were used to assess validity. Reproducibility was shown to be statistically significant, with coefficients ranging from 0.72 to 0.74 between dimensions of three interviews. The Cronbach alpha coefficients were 0.96 and 0.90 respectively for the dimensions of the interviews and for total items. Constructive validity, demonstrated through a comparison between the questionnaire dimensions and the clinical parameters, showed statistical significance for "presence of carious lesion" (p < 0.05). Significant correlations between similar dimensions of the OHIP-49 and the SF-36 were also identified (p < 0.05). In the present sample, the Portuguese version of the OHIP-49 presented results similar to those found in the literature and proved to be a reproducible and valid parameter for evaluating the impact of oral conditions on the quality of life of Brazilians. O objetivo deste estudo é desenvolver uma versão na língua portuguesa do OHIP-49 para ser utilizado no Brasil. A metodologia utilizada consiste de tradução, tradução de volta e revisão da tradução inicial, adaptação cultural e avaliação das propriedades de medida. O questionário foi aplicado, por meio de entrevistas, em brasileiros com 60 ou mais anos. Utilizou-se o coeficiente de correlação Kendall-tau para testar reprodutibilidade, coeficiente alfa de Cronbach para consistência interna e testes de Kruskal-Wallis e Mann-Whitney para validação. A reprodutibilidade demonstrou ser estatisticamente significante, com os coeficientes variando de 0,72 a 0,74, entre as dimensões de três entrevistas. Os coeficientes alfa de Cronbach foram iguais a 0,96 e 0,90, para as dimensões das entrevistas e para o total de itens, respectivamente. A validade construtiva, demonstrada pela comparação das dimensões do questionário com os parâmetros clínicos apresentou-se estatisticamente significante para "presença de lesão cariosa" (p < 0,05). Foram identificadas correlações significantes entre dimensões similares do OHIP-49 e do SF-36 (p < 0,05). Nesta amostra, a versão em português do OHIP-49 apresentou resultados semelhantes aos da literatura, demonstrou ser um parâmetro reprodutível e válido para avaliar impactos das condições bucais na qualidade de vida de brasileiros.